2010
DOI: 10.1007/s13258-010-0033-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and marker-trait associations in a collection of Pak-choi (Brassica rapa L. ssp. chinensis Makino) Accessions

Abstract: Pak-choi (Brassica rapa L. ssp. chinensis Makino) is one of the most important vegetable, especially in southern China. Morphological traits of Pak-choi vary widely, and the genetic basis of these variations is largely undescribed. In this study, we evaluated eighty Pak-choi accessions for genetic diversity based on 29 morphological descriptors and 20 microsatellite (SSR) loci. Our data reveal a high level of diversity in this set of Pak-choi accessions. Euclidean distance was used for cluster analysis. The UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…According to Li et al (2011), correction factors concerning population structure and relative kinship are very crucial even though both had relatively small effect on markertrait association. Our findings are consistent with results from other studies on pak-choi (Yu et al, 2010) and Brassica rapa (Pino Del Carpio et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to Li et al (2011), correction factors concerning population structure and relative kinship are very crucial even though both had relatively small effect on markertrait association. Our findings are consistent with results from other studies on pak-choi (Yu et al, 2010) and Brassica rapa (Pino Del Carpio et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that the marker-trait association attained in model GLM without Q was due to population structure. The inclusion of population structure and relative kinship reduce type I error, thus eliminating false positive associations (Yu et al, 2010). According to Li et al (2011), correction factors concerning population structure and relative kinship are very crucial even though both had relatively small effect on markertrait association.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] and G2 (BcL.1-25 vs BcL. [1][2][3][4] groups, a total of 313 common genes were up-regulated and 308 common genes were down-regulated ( Figure 2A and 2B); while between G1 (BcL.1-25 vs BcL. and G3 (BcL.1-4 vs BcL.…”
Section: Quantity Statistics and Veen Diagram Of Differentially Exprementioning
confidence: 99%
“…One of the most common cultivated vegetables in China, non-heading Chinese cabbage (Brassica rapa ssp. chinensis), also known as Pak-choi, while its growth are often affected, from the surroundings by cold even freezing stresses [1,2]. Low temperature, well known, as an important factor, affecting growth and reducing productivity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…SSR markers have been utilized in genetic diversity analysis of Pak-choi. Yu et al (2010) evaluated the genetic diversity of 80 Pak-choi inbred lines using 20 SSR markers. However, to date, no studies related to varietal identification in Pak-choi have been reported.…”
mentioning
confidence: 99%